Reply to: Charlier et al. 2018. Mudslide and/or animal attack are more plausible causes and circumstances of death for AL 288 ('Lucy'): a forensic anthropology analysis. Medico-Legal Journal 86(3) 139–142, 2018. (September 2019) - Kappelman, John; Ketcham, Richard A; Pearce, Stephen; Todd, Lawrence; Akins, Wiley; Colbert, Matthew W; Davis, Christopher; Feseha, Mulugeta; Maisano, Jessica A; Witzel, Adrienne
The Pliocene hominin fossil 'Lucy' (A.L. 288-1, Australopithecus afarensis ) was discovered in the Afar region of Ethiopia in 1974 and dates to 3.18 million years in age. In Kappelman et al., 1 we presented the results of a detailed investigation of the skeleton that for the first time identified and described unusual bone-into-bone compressive fractures at several of the major long bone joints. Using multiple criteria, we concluded that these fractures are more likely to be perimortem than postmortem in nature. We next evaluated a number of possible mechanisms that could have produced these fractures and, on the basis of all of the evidence, hypothesised that a fall from considerable height, likely out of a tree, with its resulting vertical deceleration event, most closely matched the pattern of fractures preserved in the skeleton and was also the probable cause of death. Charlier et al. disagree with our approach and hypothesis, and instead present what they consider to be better evidence supporting two of the other possible mechanisms for breakage that we also investigated, a mudslide/flood, or an animal attack. We here show that the evidence presented by Charlier et al. is incorrectly interpreted, and that these two alternative hypotheses are less likely to be responsible for the fractures.